Hair cluster detection model based on dermoscopic images - Xiong, Ya; Yu, Kun; Lan, Yujie; Lei, Zeyuan; Fan, Dongli (Frontiers in Physics, 2024)
Hair loss has always bothered many people, with numerous individuals potentially facing the issue of sparse hair. Due to a scarcity of accurate research on detecting sparse hair, this paper proposes a sparse hair cluster detection model based on improved object detection neural network and medical images of sparse hair under dermatoscope to optimize the evaluation of treatment outcomes for hair loss patients. A new Multi-Level Feature Fusion Module is designed to extract and fuse features at different levels. Additionally, a new Channel-Space Dual Attention Module is proposed to consider both channel and spatial dimensions simultaneously, thereby further enhancing the model's representational capacity and the precision of sparse hair cluster detection. After testing on self-annotated data, the proposed method is proven capable of accurately identifying and counting sparse hair clusters, surpassing existing methods in terms of accuracy and efficiency. Therefore, it can work as an effective tool for early detection and treatment of sparse hair, and offer greater convenience for medical professionals in diagnosis and treatment.